24-HOUR CENTRAL BLOOD PRESSURE PROFILE IN TYPE 1 DIABETICS. (June 2018) - Jankowski, P.; Kusak, P.; Bednarek, A.; Klupa, T.; Malecki, M.; Windak, A.; Czarnecka, D.
Abstract : Objective: There is an increasing evidence that central blood pressure (CBP) is more strongly correlated with target organ damage and cardiovascular events than peripheral blood pressure (PBP). 24-hour profile of CBP differs significantly from PBP, however, 24-hour profile of CBP in subjects with type 1 diabetes has been never studies so far. Therefore our goal was to compare 24-hour profile of CBP and PBP in subjects with and without type 1 diabetes. Design and method: The study group consisted of 60 patients with type 1 diabetes (age 40.0 ± 14.0 years, 20 men), whereas 86 subjects without diabetes (age 50.9 ± 15.8 years, 42 men) served as the control group. CBP and its 24-hour profile was measured using the MOBIL-O-GRAPH device, a validated oscillometric device, using a transfer function. Results: The 24-hour PBP was 122.9 ± 9.5/79.3 ± 6.7 mmHg in diabetics vs. 128.5 ± 11.2/83.4 ± 8.8 mmHg in non-diabetics (p < 0.05 for both), whereas 24-hour CBP was 112.6 ± 8.5/77.4 ± 6.6 mmHg in diabetics vs. 118.2 ± 10.4/81.6 ± 8.9 mmHg in non-diabetics (p < 0.05 for both). The differences were not significant after adjustment for age and sex. The 24-hour systolic BP amplification was 10.5 ± 3.0 mmHg vs. 10.4 ± 3.1 mmHg (p = NS both in univariate and multivariate analysis). The nighttime drop in central systolic and diastolic BP did not differ between pts with and without diabetes (6.9 ± 6.3% vs. 6.6 ± 6.3% and 13.2 ± 6.2% vs. 13.2 ± 7.5%, p = NS both in univariate and multivariate analysis). Diabetes was not related to the 24-hour pulse wave velocity when adjusted for mean BP and age. Conclusions: We did not find any significant relation between type 1 diabetes and 24-hour central hemodynamics.